2016
DOI: 10.1089/end.2016.0087
|View full text |Cite
|
Sign up to set email alerts
|

Using 300 Pretreatment Shock Waves in a Voltage Ramping Protocol Can Significantly Reduce Tissue Injury During Extracorporeal Shock Wave Lithotripsy

Abstract: Purpose: Pretreating a pig kidney with 500 low-energy shock waves (SWs) before delivering a clinical dose of SWs (2000 SWs, 24 kV, 120 SWs/min) has been shown to significantly reduce the size of the hemorrhagic lesion produced in that treated kidney, compared with a protocol without pretreatment. However, since the time available for patient care is limited, we wanted to determine if fewer pretreatment SWs could be used in this protocol. As such, we tested if pretreating with 300 SWs can initiate the same redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…It was reported that pretreatment with 300-500 low-energy (12 kV) SWs before delivering the clinical dose of SWs (2000 SWs, 24 kV) was associated with a protective response in treated pigs. 16,17 Connors et al reported that the interval (3-4 min pause) between the initial 100 SWs and the clinical dose of SWs is more important for protecting the kidney rather than starting at low voltage. 7 This protocol of pretreatment with low-voltage 100 shocks (12 kV) with 3-min intervals before the clinical dose was also proved to significantly reduce acute oxidative stress and inflammation in the treated porcine kidney.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that pretreatment with 300-500 low-energy (12 kV) SWs before delivering the clinical dose of SWs (2000 SWs, 24 kV) was associated with a protective response in treated pigs. 16,17 Connors et al reported that the interval (3-4 min pause) between the initial 100 SWs and the clinical dose of SWs is more important for protecting the kidney rather than starting at low voltage. 7 This protocol of pretreatment with low-voltage 100 shocks (12 kV) with 3-min intervals before the clinical dose was also proved to significantly reduce acute oxidative stress and inflammation in the treated porcine kidney.…”
Section: Resultsmentioning
confidence: 99%
“…Other renal protective protocols were also proved in animal studies. It was reported that pretreatment with 300–500 low‐energy (12 kV) SWs before delivering the clinical dose of SWs (2000 SWs, 24 kV) was associated with a protective response in treated pigs . Connors et al .…”
Section: Discussionmentioning
confidence: 99%
“…When compared to a fixed voltage protocol ramping improves SFR, while renal damage as measured by urinary excretion of microglobulins is decreased [71] , [72] , [73] . Recently, using a porcine model, it was shown that pretreatment (300–500 shocks) at a low voltage without a pause decreases damage to the kidney [74] , [75] . A recent clinical trial supports these in vitro results; stepwise voltage ramping was associated with a lower risk of hematoma (odds ratio 0.39) when compared to a fixed maximal voltage protocol [76] .…”
Section: Improving Outcomes and Preventing Complicationsmentioning
confidence: 99%
“…Limitations of our study are the moderate questionnaire response rate and the unavailable information regarding hypertension or diabetes at time-point of SWL. Additionally, currently used lithotripter, newer settings (e.g., ramping [ 20 , 21 ]) and co-current medications [ 22 ] have been discussed to reduce damage to the kidneys but were not used in this study. Nevertheless, in the absence of prospective data from larger cohorts with an appropriate follow-up, our study is a unique and valuable opportunity to study long-term adverse effects.…”
Section: Discussionmentioning
confidence: 99%